Study guides

☆☆

Q: How do you solve -3y plus x equals 7?

Write your answer...

Submit

Related questions

4x + 3y = 7 y = [(-4)/3] x + 7/3

Fsxjugfxbi

5y+14+y = 3y-7 5y+y-3y = -7-14 3y = -21 y = -7

Solve for y 3y=-7x+9 y=-7/3x+3 the slope is the coefficient of x in this case, it is -7/3

If: -x-3y = -4 and 3x+5y = 16 Then: x = 7 and y = -1

(5, 1)

x + 8y = 3 therefore 2x + 16y = 6 (a) 2x + 3y = -7 (b) Subtract (b) from (a): 13y = 13 so y = 1 and x = -5

You need to organise your question properly. 3x+2y=4 4x + 3y= 7? Is 4 4x = 44x or 4-4x or 4+4x How can there be 2 equal signs in 1 equation?

are you talking about a system of equations where x+3y=-7 -x+2y=-8 if so, then the answer is {2,-3}

{-4,-5}

7

x2 + 3y = 7 3x + y2 = 3 3y = x2 + 7 y2 = -3x + 3 y = x2/3 + 7/3 y = ± √(-3x + 3) If you draw the graphs of y = x2/3 + 7/3 and y = ± √(-3x + 3) in a graphing calculator, you will see that they don't intersect, so that the system of the given equations has not a solution.

X equals 1 and so does Y

-3y + 6 = 7 Therefore, -3y = 1 Therefore, y = 1/-3 Therefore, y = -0.3 recurring (that is, -0.3333...)

4y + 7 - y = 10 + 3y My next step is to combine the y's on the left, 3y + 7 = 10 + 3y If I then subtract 3y from both sides I obtain 7 = 10 which is not a true statement. Hence, the equation that you presented is invalid.

3y plus 7 makes a tomato pie and 1-y is .....em.......oh look at that it is past my bedtime! Cheerio!

given is that 4x+3y=6(3x+3y)=7 i.e., 6(3x+3y)=7 &&& 4x+3y=7 ---------------(1) 3x+3y=7/6 x+y=7/18 _________(2) multiply eqn(2) by 4 4x+4y=28/18 -------------------------(3) (3)-(1) 4x+3y-4x-4y=7-(28/18) y= -98/18 substitute y in eqn(2) x-98/18=7/18 x=7/18+98/18 x=105/18. therefore x=105/18 : y= -98/18

x=2 y=7 5x+3y= 5 7 x 2 x 3 ____ _____ 10 21 21 + 10 _______ 31

4

4y + 7 = 3y + 9-3y-7 -3y-7y = 24(2) + 7 = 3(2) + 98 + 7 = 6 + 915 = 15

y=5x+2 if y equals -4

7 + 8y - 3y + 2 =7 + 2 + 8y - 3y = 9 + 8y - 3y = 9 + 5y

4y + 7 < 3y + 9 4y - 3y < 9 - 7 y < 2

4x - 3y = -7 Change all signs: -4x + 3y = 7 Add 4x to both sides: 3y = 4x + 7 Divide both sides by 3: y = (4/3)*x + 7/3 m = 4/3, b = 7/3

n= -2